Метод розпізнання клавіатурного почерку користувачів комп’ютерних мереж на основі на основі dtw-алгоритму - Ожоганич, О. В. (ХНУРЕ, 2019)
The focus of the research is biometric recognition systems. The study subject is person authentication via keystroke dynamics. The algorithm of keystroke authentication based on the DTW algorithm is developed